P154 Safety of tiotropium in pre-school children with symptomatic persistent asthma. (15th November 2016) - Bisgaard, H; Vandewalker, M; Graham, L; Moroni-Zentgraf, P; Engel, M; Azzi, G El; Vulcu, SD; Finnigan, H; Vrijlandt, EJLE
Abstract : Introduction and objectives: Asthma is the most common chronic disease of childhood (GINA 2015). For pre-school children whose asthma symptoms are not well controlled on inhaled corticosteroids, limited options are available for further treatment. Here, we evaluated the safety of once-daily (QD) tiotropium Respimat® (tioR) in patients aged 1–5 years with symptomatic persistent asthma. Methods: A Phase II/III, randomised, double-blind, placebo-controlled, parallel-group trial (NCT01634113 ) of tioR 5 μg, tioR 2.5 μg or placebo Respimat® (pboR), administered QD in the afternoon for 12 weeks, each as add-on to usual maintenance therapy. Safety data, including post hoc analysis of a composite exacerbation end point derived from adverse events (AEs), are reported. Results: No AEs leading to treatment discontinuation or death were reported. The proportion of patients with any AEs was higher with pboR (73.5%) than with tioR 5 μg (58.1%) and 2.5 μg (55.6%). Two patients each in the tioR 5 μg (6.5%) and pboR (5.9%) groups were reported with drug-related AEs. Three patients, all in the pboR group, were reported with serious AEs. Asthma exacerbation/worsening was reported by fewer patients in the tioR 5 μg and tioR 2.5 μg groups compared with the pboR group (Table). Conclusion: Once-daily tiotropium Respimat® add-on to maintenance therapy is well tolerated and may reduce exacerbations in pre-school children with symptomatic persistent asthma.